A personalized 3D-printed prosthetic joint replacement for the human temporomandibular joint: From implant design to implantation. (May 2017) - Ackland, David C.; Robinson, Dale; Redhead, Michael; Lee, Peter Vee Sin; Moskaljuk, Adrian; Dimitroulis, George
Abstract: Personalized prosthetic joint replacements have important applications in cases of complex bone and joint conditions where the shape and size of off-the-shelf components may not be adequate. The objective of this study was to design, test and fabricate a personalized 3D-printed prosthesis for a patient requiring total joint replacement surgery of the temporomandibular joint (TMJ). The new 'Melbourne' prosthetic TMJ design featured a condylar component sized specifically to the patient and fixation screw positions that avoid potential intra-operative damage to the mandibular nerve. The Melbourne prosthetic TMJ was developed for a 58-year-old female recipient with end-stage osteoarthritis of the TMJ. The load response of the prosthesis during chewing and a maximum-force bite was quantified using a personalized musculoskeletal model of the patient's masticatory system developed using medical images. The simulations were then repeated after implantation of the Biomet Microfixation prosthetic TMJ, an established stock device. The maximum condylar stresses, screw stress and mandibular stress at the screw-bone interface were lower in the Melbourne prosthetic TMJ (259.6 MPa, 312.9 MPa and 198.4 MPa, respectively) than those in the Biomet Microfixation device (284.0 MPa, 416.0 MPa and 262.2 MPa, respectively) during the maximum-force bite, with similar trends also observed during the chewing bite. After trialing surgical placement and evaluating prosthetic TMJ stability using cadaveric specimens, the prosthesis was fabricated using 3D printing, sterilized, and implanted into the female recipient. Six months post-operatively, the prosthesis recipient had a normal jaw opening distance (40.0 mm), with no complications identified. The new design features and immediate load response of the Melbourne prosthetic TMJ suggests that it may provide improved clinical and biomechanical joint function compared to a commonly used stock device, and reduce risk of intra-operative nerve damage during placement. The framework presented may be useful for designing and testing customized devices for the treatment of debilitating bone and joint conditions. Graphical abstract: Highlights: A personalized joint replacement for the human jaw was designed and tested. The prosthesis reduces risk of intra-operative nerve damage. The prosthesis stresses were lower than those of a stock implant during biting. The prosthesis was fabricated using rapid prototyping. Postoperatively, the implant recipient had a normal jaw opening distance.